El Excentrico, 1958-05-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 5, 1958 [5 de mayo de 1958]. Ano 8, No. 17. There are two editions for this issue. The first edition's cover contains a photo of John M. Klarich, who was running for an election that took place in Gilroy. This cover serves as a flyer encouraging viewers to vote for him on election day, which took place on June 3, 1958. The second editions cover contains a photo of Carolyn Edney posing in front of a car with car show attendees at the side. This cover serves as a flyer for the Volantes Beauty-Car Show that took place at the I.E.S. Hall on May 25. The headline of this cover reads, "Lovely Carolyn Edney gets Club Volantes Beauty-Car Show underway."